La escuela neoliberal en la Comunidad de Madrid. Estrategias y prácticas políticas, 2003-2015. - Ramírez Aísa, Elías (Historia y Memoria de la Educación, 2016)
The politics of education can be analyzed from two points of view: as a structure, one that affects institutions and the rules that regulate them, and as a process one that focuses on the behaviour of those involved and on outcomes. This article deals with the politics of education as seen in outcomes, this being the essential core of the policies implemented in the field of education by the Partido Popular in Madrid. As we will see, the measures undertaken make this region a genuine laboratory of neoliberal and neoconservative educational practices. We will observe how we are facing coherent educational practices, guided predominantly by the neoliberal ideology: an instrumental design of administrative organization in keeping with the government’s ideology and political orientation; an increasing and shameless process of privatization of educational opportunities; the primacy of school choice on the families’ part which, together with the defense and promotion of the schools’ autonomy, inevitably leads to the triumph of competition within the educational market, thus completing the link between the sum of the educational goods and the satisfaction of the family desires; a differentiated curriculum and a proposed evaluation of the subjects. Under the guise of traditional education, this endorsement of a culture of effort, talent and individual merit are meant to come together under the equivocal concept of excellence. This approach, which, takes a suspicious view of laicism, also takes a posture clearly favouring conservative groups and even religious institutions, all intent on creating educational centres that will vehemently defend the liberal and spiritual ideologies and the political system they support.